On the Malmquist Theorem for Solutions of Differential Equations in the Neighborhood of an Isolated Singular Point - Mokhonko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
The statement of the Malmquist theorem (1913) about the growth of meromorphic solutions of the differential equation \(f’ = P(z,f) Q(z,f) \), where P(z, f) and Q(z, f) are polynomials in all variables, is proved in the case of solutions with isolated singular point at infinity.